La investigación en Administración - Pineda Henao, Elkin Fabriany; Tello Castrillón, Carlos; Rivera Godoy, Jorge Alberto; Roa Correa, Andrea; Sarasty Crespo, Carolina; Galvis Galvis, Ana Cristina; Quintero Sepulveda, Isabel Cristina; Pérez de Paz, María; Reyes Barreto, Edwin Manuel; Bolaños Perea, Jhon Henry; Ochoa Muñoz, Andrés Felipe; González Rojas, Yeraldine; et al. (Universidad Santiago de Cali, 2025)
Published